Case Report: Reversible Neurotoxicity and a Clinical Response Induced by BCMA-Directed Chimeric Antigen Receptor T Cells Against Multiple Myeloma With Central Nervous System Involvement - Zhang, Ying; Zhang, Changfeng; Zhou, Jin; Zhang, Jingren; Chen, Xiaochen; Chen, Jia; Wang, Pu; Sun, Xiuli; Lou, Xiaoyan; Qi, Wei; Kang, Liqing; Yu, Lei; et al. (Frontiers in Immunology, 2021)
Isolated central nervous system involvement in multiple myeloma (CNS-MM) is rare and carries extremely poor prognosis. Chimeric antigen receptor T cell therapy (CART) targeting B-cell maturation antigen (BCMA) is demonstrated as a promising strategy in MM treatment, but the clinical safety and efficacy of BCMA-CART against isolated CNS-MM remain elusive. Here we report on a 56-year-old male with refractory isolated CNS-MM who received autologous BCMA-CART therapy and developed grade 4 neurological complications. Cerebrospinal fluid (CSF) analyses showed significant expansion of CART cells and a substantially elevated interleukin-6 (IL-6) level. Intravenous methylprednisolone was administered and the symptoms resolved gradually. Unexpectedly, the level of IL-6 in the CSF was maintained for another 3 days even after the relief of the neurological symptoms. A partial response was achieved and sustained for 5.5 months. This is the first report describing a patient with isolated CNS-MM treated using BCMA-CART therapy. The results demonstrated that BCMA-CART cells administered intravenously trafficked into the CSF, eradicated tumor cells, and induced severe but reversible neurological adverse events. This single-patient report suggests that BCMA-CART therapy can be considered as an alternative option for isolated CNS-MM. Clinical Trial Registration ClinicalTrials.gov, identifier NCT03196414.